Murder at the Porte de Versailles - Black, Cara, 1951- (The Aimeé Leduc investigations, 2022)
"November, 2001: in the wake of 9/11, Paris is living in a state of heightened fear, with constant bomb alerts and heightened ethnic tension. For Aimée Leduc, November is bittersweet: the anniversary of her father's death and her daughter's third birthday fall on the same day. A gathering for family and friends is disrupted when a bomb goes off at the police laboratory-and Boris Viard, the partner of Aimée's friend Michou, is found unconscious at the scene of the crime, his fingerprints on the bomb fragments. Aimée doesn't believe Boris set the bomb. In an effort to prove him not guilty, she battles the police and his own lab colleagues, collecting conflicting eyewitness reports. When a member of the French secret service drafts Aimée to help investigate possible links to an Iranian Revolutionary guard and fugitive radicals who bombed Interpol in the 1980s, Aimée uncovers ties to a cold case of her father's. As Aimée scours the streets of Teheran-sur-Seine trying to learn the truth, she has to ask herself if she should succumb to pressure from Chloe's biological father and move them out to his farm in Brittany"--